2011
DOI: 10.2139/ssrn.1799402
|View full text |Cite
|
Sign up to set email alerts
|

Cross Hedging Under Multiplicative Basis Risk

Abstract: Cross hedging price risk in an incomplete financial market creates basis risk. We propose a new way of modeling basis risk where price risk and basis risk are combined in a multiplicative way. Under this specification, positive prudence is a necessary and sufficient condition for underhedging in an unbiased market. Using the example of cross hedging jet fuel price risk with crude oil futures, we show that the new specification is superior in describing the price series and that optimal cross hedges differ sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Coffee (traded on NYBOT), cotton (NYMEX), corn (CBOT) and crude oil (NYMEX) prices from January 1986 through December 2010, a total of 300 months, were obtained from Datastream. In the context of futures hedging, monthly data has been explored previously in a number of studies due to a reduction in nonsynchroneity problems between futures and cash (Adam-Müller & Nolte, 2011;Ederington & Salas, 2008). Monthly data is appropriate in this study, as it allows contrast to studies of corporate finance hedging policy where the reported data ranges from monthly horizon up to five years (Jin & Jorion, 2006;Allayannis & Ofek, 2001;Haushalter, 17 Confidence intervals for the wavelet variance and covariance may be calculated using large sample theory.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…Coffee (traded on NYBOT), cotton (NYMEX), corn (CBOT) and crude oil (NYMEX) prices from January 1986 through December 2010, a total of 300 months, were obtained from Datastream. In the context of futures hedging, monthly data has been explored previously in a number of studies due to a reduction in nonsynchroneity problems between futures and cash (Adam-Müller & Nolte, 2011;Ederington & Salas, 2008). Monthly data is appropriate in this study, as it allows contrast to studies of corporate finance hedging policy where the reported data ranges from monthly horizon up to five years (Jin & Jorion, 2006;Allayannis & Ofek, 2001;Haushalter, 17 Confidence intervals for the wavelet variance and covariance may be calculated using large sample theory.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…Franke et al [23] proposed conditions for multiplicative risk vulnerability. Furthermore, Franke et al [24] studied the simultaneous effect of both additive and multiplicative risks and explained some paradoxical choice behavior. In the field of hedging, Adam-Müller and Nolte [25] proposed a model with multiplicative background risk.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we introduce multiplicative background risk to affect both the spot and futures prices in a symmetric manner, which is more suitable to model credit risk or inflation risk. Because of the asymmetric treatment of the multiplicative background risk on the firm's payoff function, Adam-Müller and Nolte (2011) show that prudence in the sense of Kimball (1990Kimball ( , 1993 is called for to yield unambiguous futures positions.…”
mentioning
confidence: 99%